Control of incomplete separation in simulated moving bed chromatographic processes. Issue 7 (2016) - Suvarov, Paul; Wouwer, Alain Vande; Lee, Ju Weon; Seidel-Morgensten, Andreas; Kienle, Achim
Abstract: Simulated moving bed (SMB) is a continuous chromatographic process used for the separation of fluid mixtures. This paper presents a simple control strategy to handle incomplete separation, which requires tight control to achieve the desired purities. At first, a discrete-time nonlinear model is derived from wave theory, which will be the basis to estimate the position of the adsorption and desorption fronts. Four controllers are designed, two for the position of the concentration waves in zone 1 and 4, and two for the purities at the extract and raffinate outlets. The performance of the control strategy is evaluated with an experimental study of the separation of racemic Bicalutamide enantiomers in a 4 column-SMB.